বিপন্ন বাংলাদেশ : রাষ্ট্র,সমাজ ও উন্নয়নের এনজিও মডেল - আজাদ, লেনিন. (ঢাকা : প্রাচ্যবিদ্যা প্রকাশনী, 1997)
Articles on the economic development of Bangladesh and the role of Non-governmental organizations in Bangladesh.
In Bengali.
Keywords: Non-governmental organizations -- Bangladesh; Bangladesh -- Economic conditions